Magnetic Recording Fidelity of Basalts Through 3D Nanotomography - Hristo Gergov; Adrian R. Muxworthy; Wyn Williams; Alison C. Cowan (Geochemistry, Geophysics, Geosystems)
Abstract Volcanic basalt samples originating from two historic eruptions, that is, the 1991 C.E. Hekla, Iceland, and 1944 C.E. Vesuvius, Italy, have been studied to determine the 3D tomographic and spatial distributions of their constituent (titano)magnetite minerals using SEM‐FIB slice‐and‐view. Determining the morphology is key to quantifying the magnetic recording fidelity of a rock, as grain morphology is a primary control of the magnetic (domain) state of a grain, which in turn determines magnetic recording fidelity. Smaller grains are magnetically uniform and are termed single domain (SD). A surface morphology resolution of ∼2 nm was achieved and the smallest grains that were resolved with ∼21 nm in diameter; a total of 971 particles were analyzed. We determined a median equivalent‐volume spherical diameter of 70 nm for the Hekla sample, and 135 nm for the Vesuvius sample. The particles had nearest‐neighbor distances of 184 and 355 nm, indicate the majority of grains were free from magnetostatic interactions. In both samples there was a roughly even split between oblate and prolate grains. This number of oblate grains is much higher than traditionally assumed, and will have implications for many paleomagnetic methods which assume prolate grains, for example, anisotropy of magnetic susceptibility analysis. Numerical micromagnetic analysis of the grain‐morphologies, predict that ∼64% of the Hekla grains have SD ground‐states (∼6% by volume), but only ∼26% of the Vesuvius grains have SD ground‐states (∼1% by volume). Both samples are predicted to be excellent paleomagnetic recorders, with median relaxation times far larger than the length of the Universe.